2014
DOI: 10.1007/s00264-014-2329-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of symptomatic venous thrombo-embolism following shoulder surgery

Abstract: Purpose This clinical study was performed to establish the incidence of symptomatic deep vein thrombosis and pulmonary embolism after shoulder surgery as the incidence of venous thrombo-embolism complicating shoulder surgery is poorly described in literature. Methods We reviewed retrospectively clinical records of 920 consecutive patients who had any surgical procedure performed on their shoulder in Glan Clwyd Hospital, North Wales and a further 1,421 consecutive patients who had surgery in Morriston and Singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
(13 reference statements)
0
14
0
Order By: Relevance
“…The incidence of PE after shoulder arthroscopy has been reported to be 0.01%–0.13% 1,7,10–15 . A study by Jameson et al 11 ,.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of PE after shoulder arthroscopy has been reported to be 0.01%–0.13% 1,7,10–15 . A study by Jameson et al 11 ,.…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that mechanical prophylaxis does not necessarily contribute to a lower incidence of VTE, many researchers still think routine chemoprophylaxis for perioperative VTE in shoulder arthroscopy patients is unnecessary, in view of its low incidence and the potential adverse drug reactions of anticoagulants. The majority of researchers recommend an implementaiton of chemoprophylaxis in patients at a high risk of VTE, particularly when multiple risk factors coexist 2,15,17,29 . Chemoprophylaxis should be based on the substantial estimation of individual risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Available literature reports wide variability in the incidence of VTE events following shoulder arthroplasty, with estimates ranging from 0.2%-16% 101-116 . However, these studies varied significantly in how VTE events were identified.…”
Section: Question: 7 - Should Routine Chemical Vte Prophylaxis Be Adm...mentioning
confidence: 99%
“…Two articles did not provide baseline characteristics to assess the number of each surgical procedure performed. 27,35 These surgical procedures were performed for a range of indications, of which 73% were due to osteoarthritis, with the remaining procedures due to proximal humeral fractures, inflammatory arthropathy, rotator cuff arthropathy, osteonecrosis and failed primary operations (Table 2). The mean age of patients was 66.5 years.…”
Section: Shoulder Arthroplastymentioning
confidence: 99%
“…Mortality secondary to VTE was reported in four articles, each reporting a single case from a total of 634 patients. 16,18,22,27 Other complications including post-thrombotic syndrome and clot extension triggering cardiac involvement were not reported.…”
Section: Shoulder Arthroplastymentioning
confidence: 99%